Cover Image. Issue 10 (12th September 2018) - Luo, X; Liao, G; Liu, C; Jiang, X; Lin, M; Zhao, C; Tao, J; Huang, Z
Abstract : The cover image, by X Luo et al., is based on the Original Article Characterization of bacteriophage HN48 and its protective effects in Nile tilapia Oreochromis niloticus against Streptococcus agalactiae infections, DOI:10.1111/jfd.12838 .